Crosswinds : the Air Force's setup in Vietnam - Tilford, Earl H. (Texas A & M University Press, 1993)
Who lost the war in Vietnam? Popular mythology has blamed politicians, the press, or Jane Fonda and the antiwar movement. Crosswinds, a riveting and incisive analysis by a former Air Force officer who served as an intelligence specialist during the war, demonstrates convincingly that the U.S. Air Force was indeed "set up" for defeat, but not by an America that tied its hands. Rather, the Air Force was a victim of its own history, its institutional values, and an intellectually ossified leadership which could not devise a strategy appropriate to the war at hand. These factors within the Air Force itself created heavy flying.
Keywords: United States. -- Air Force -- History -- Vietnam War, 1961-1975.; United States. -- Air Force; Vietnam War, 1961-1975 -- Aerial operations, American.; Guerre du Viêt-nam, 1961-1975 -- Opérations aériennes américaines.; HISTORY -- Military -- Vietnam War.; Military operations, Aerial -- American; 1961-1975; History